Synthesis and characterisation of hybrid graft copolymers of polydimethylsiloxane and polymethylmethacrylate - Krugel, Gretha (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.